The alienist. Season 1. [videorecording (DVD)] - Carr, Caleb, 1955-; Brühl, Daniel, 1978-; Evans, Luke, 1979-; Geraghty, Brian; Wisdom, Robert; Smith, Douglas, 1985-; Shear, Matthew, 1984-; Kilcher, Q'Orianka; Lintz, Matt, 2001-; Fanning, Dakota, 1994-; Carr, Caleb, 1955- (Warner Bros. Home Entertainment, 2019)
Dr. Laszlo Kreizler treats mental pathologies -- a controversial new field in 1896 -- and it may unlock the secret to another new phenomenon: a ritualistic serial killer who is targeting young boys in New York City.